O morar permanente na praia: moradia e vilegiatura na localidade praiana do Icaraí - CE - Silveira, Bruno Rodrigues da (2011)
This dissertation shows careful consideration about the process of transformation of the residences used as second homes or beach houses into permanent residences in the coast of Caucaia having as study case beach of Icaraí The process of transmutation in the coastal area is conducted by economical and social transformation factors of RMF Being in a dense occupation housing area and near the west zone of Fortaleza beach of Icaraí is an appropriate location for permanent residence In the investigation we applied questionnaires in 51 condominiums and 36 houses in Icaraí At first the questionnaires were applied to care-takers and porters and at the second directly to the residents Analysis on the results of the 2010 IBGE’s demographic census and research on ‘O Povo’ newspaper data bank were also carried out This research reveals an increase on the occupation rate of houses and apartments in the last 10 years This was a consequence of urban expansion to the coast of Caucaia and real estate market actions and investments in housing Some factors helped boosting this crescent sector in Icaraí such as: improvement on access roads and transportation; the presence of an active commercial sector in the location; decrease on prices of land and properties caused by the erosion processes at the beach; Pecém port creation; and mainly incentives for financing property buying through the federal housing program – Minha Casa Minha vida